Participatory sensing in Kenya :: Preconditions for successful implementation - Kalui, Dorothy Mwongeli; Muketha, Geoffrey Muchiri; Onsomu, Jared (African Journal of Science, Technology and Social Sciences, 2025)
An increasing number of participatory sensing applications have been developed in recent years. Since these applications can be used for personal and community levels to address real world problems, the players of location based services (LBS) are already exploring their environment. One approach could be to especially address these users’ necessary preconditions for successful implementation in order to increase the Kenyan user base of participatory sensing applications. To achieve this objective, a number of earlier related studies were reviewed with a view of identifying factors affecting successful implementations in Kenya for use in the study. To this end, we conduct a questionnaire-based study involving 100 participants to investigate the possible key preconditions necessary for successful implementation of LBS. In particular, we analyze the potential interests of our participants in sensing tasks based on their demographics and interaction with sensing applications. It results to proposed preconditions of successful implementation in Kenya. The identified preconditions are tested statistically using correlation and regression analysis. The findings based on Pearson correlation analysis (coefficients above 0.8) indicate the preconditions have strong linear relationship and recorded p-values of less than 0.05 meaning that their contribution is significant to successful implementation in Kenya.